Deformation mechanism in nanolaminate FeCrAl alloys by in situ micromechanical strain rate jump tests at elevated temperatures. (1st July 2022) - Sun, Tianyi; Cho, Jaehun; Shang, Zhongxia; Niu, Tongjun; Ding, Jie; Wang, Jian; Wang, Haiyan; Zhang, Xinghang
Abstract: FeCrAl alloys have attracted extensive attention as one of the potential cladding materials for the commercial light water reactors. Although the creep behaviors of coarse-grain FeCrAl alloys have been investigated at elevated temperatures, little is known on the deformation mechanism of fine-grain FeCrAl alloys. Here, we performed surface mechanical grinding treatment to fabricate nanolaminated ferritic FeCrAl alloys. In situ micropillar compression tests were applied to determine the underlying deformation mechanism of nanolaminated FeCrAl alloys at elevated temperatures. The strain rate sensitivity and activation energy for the dominant deformation mechanism were estimated considering the presence of a threshold stress. Graphical abstract: Image, graphical abstract